2019
DOI: 10.1007/s10549-019-05174-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel RNA aptamer identifies plasma membrane ATP synthase beta subunit as an early marker and therapeutic target in aggressive cancer

Abstract: Purpose Primary breast and prostate cancers can be cured, but metastatic disease cannot. Identifying cell factors that predict metastatic potential could guide both prognosis and treatment. Methods We used Cell-SELEX to screen an RNA aptamer library for differential binding to prostate cancer cell lines with high vs. low metastatic potential. Mass spectroscopy, immunoblot, and immunohistochemistry were used to identify and validate aptamer targets. Aptamer properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Numerous studies have revealed the roles of PM-located ATP synthase (eATP synthase) in cancers (Li et al, 2017;Lu et al, 2009;Speransky et al, 2019). In this work, we aimed to establish the mechanism responsible for the transport of eATP synthase.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous studies have revealed the roles of PM-located ATP synthase (eATP synthase) in cancers (Li et al, 2017;Lu et al, 2009;Speransky et al, 2019). In this work, we aimed to establish the mechanism responsible for the transport of eATP synthase.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, in association with KIF5B, DRP1 carries these fragmented mitochondria containing ATP synthase along the microtubules toward the cell surface. Some evidence points to a positive correlation between eATP synthase and the migratory capability of tumors (Li et al, 2017;Speransky et al, 2019). Identification of these ATP synthase trafficking-related regulators may thus provide useful information for the development of potential therapies against metastatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic Aptamers Against Prostate Cancer Cells Speransky et al (2019) designed an RNA aptamer (Apt63) to distinguish prostate cancer cell lines with high metastatic potential from low metastatic potential. Apt63 was not bound to non-metastatic cancer cells but stuck to the beta subunit of F1Fo ATP synthase (ATP5B), which existed in the plasma membrane of cancer cells.…”
Section: Therapeutic Aptamers Against Liver Cancer Cellsmentioning
confidence: 99%
“…Apt63 was not bound to non-metastatic cancer cells but stuck to the beta subunit of F1Fo ATP synthase (ATP5B), which existed in the plasma membrane of cancer cells. The binding of Apt63 and plasma membrane-located ATP synthase (Ecto-ATP5B) could destroy the basic survival mechanism of tumors with high metastatic potential and lead to rapid cell death ( Speransky et al, 2019 ). Prostate-specific membrane antigen (PSMA) is a glycosylated type II membrane protein.…”
Section: Screening and Development Of Therapeutic Aptamers Against Cancer Cellsmentioning
confidence: 99%
“…The application of angiostatin, an inhibitor of cell migration and the proliferation, binds to the α-subunit of the ecto F 1 Fo ATP synthase and inhibits angiogenesis [ 128 ]. The expression of the β-subunit of the ecto F 1 Fo ATP synthase is also higher in breast cancer cells than normal cells [ 129 ], and application of an aptamer or an antibody targeting the β-subunit induced cytotoxicity in various epithelial cells including breast cancer cells [ 129 , 130 ]. Inhibition of the β-subunit increased apoptosis and blocked phosphorylation of ERK and Akt, thus the ecto β-subunit may regulate survival genes that are under the control of the ERK and Akt pathways [ 130 ].…”
Section: Alteration Of Mitochondrial Energy Metabolismmentioning
confidence: 99%